Investigation of 3D modelling and virtual reality systems in Malaysian automotive industry. - Mousavi, Maryam; Abdul Aziz, Faieza; Ismail, Napsiah
Automotive industry uses virtual reality (VR) and three-dimensional (3D) modelling at different stages like many other industries in the world. To choose the right technology for the right purpose, it is crucial to identify the existing technology used, their benefits as well as barriers. Six automotive manufacturing companies in Malaysia were selected as case studies for this work. Investigation was performed on 3D and VR technologies used. A total number of 240 questionnaires were distributed between selected automotive industry and 153 people responded to the questionnaires. Frequency analysis was conducted followed by t-test on the respondents' answers. Based on the questionnaires, this research identified and analyzed the opportunities of 3D and VR in the industry and their constraints. The results showed that 70.6% of the respondents used 3D modeling and 38% of respondents used VR in their organization at present. It was also found that 'reducing rework' and 'improving quality of manufacturing' are the two most common advantages of using VR technology. 'Lack of knowledge', 'lack of trained people' and 'time to get proficient' are three major barriers for adopting with new technology such as YR. It is concluded that the benefits of using 3D modelling and VR outperformed the existing barriers.